Optimizing the Activity of Nanoneedle Structured WO3 Photoanodes for Solar Water Splitting: Direct Synthesis via Chemical Vapor Deposition - Kafizas,A; Francas,L; Sotelo-Vazquez,C; Ling,M; Li,Y; Glover,E; McCafferty,L; Blackman,C; Darr,J; Parkin,I (JOURNAL OF PHYSICAL CHEMISTRY C, 2017)
Solar water splitting is a promising solution for the renewable production of hydrogen as an energy vector. To date, complex or patterned photoelectrodes have shown the highest water splitting efficiencies, but lack scalable routes for commercial scale-up. In this article, we report a direct and scalable chemical vapor deposition (CVD) route at atmospheric pressure, for a single step fabrication of complex nanoneedle structured WO3 photoanodes. Using a systematic approach, the nanostructure was engineered to find the conditions that result in optimal water splitting. The nanostructured materials adopted a monoclinic γ-WO3 structure and were highly oriented in the (002) plane, with the nanoneedle structures stacking perpendicular to the FTO substrate. The WO3 photoanode that showed the highest water splitting activity was composed of a ∼300 nm seed layer of flat WO3 with a ∼5 μm thick top layer of WO3 nanoneedles. At 1.23 VRHE, this material showed incident photon-to-current efficiencies in the range ∼35–45% in the UV region (250–375 nm) and an overall solar predicted photocurrent of 1.24 mA·cm–2 (∼25% of the theoretical maximum for WO3). When coupled in tandem with a photovoltaic device containing a methylammonium lead iodide perovskite, a solar-to-hydrogen efficiency of ca. 1% for a complete unassisted water splitting device is predicted.